Geochemical cycling of phosphorus and iron in a typical reservoir in the area of Xiaoxing’an mountains, northeastern China - Bing, Xiaojie; Wang, Kuo; Ma, Huihui; Liu, Fan; Jiang, Juan; Ding, Jing; Zhu, Yuanrong; Wei, Jian (Frontiers in Environmental Science, 2022)
Reservoirs have an important impact on riverine material migration and transformation. Taking a drinking water reservoir located in the cold-temperature forest in the Xiaoxing'an Mountains, as an example, comprehensively analyze the fractions and interrelationships of phosphorus (P) and iron (Fe) from soils to riverine and reservoir’s sediments, and discuss the coordinated migration and transformation process of regional P and Fe and the effects of dam interception. The results showed that iron bound P (Fe-P), aluminum bound P (Al-P) were significantly correlated with adsorbed Fe(II), carbonate bound Fe (Fecarb), low activity silicate bound Fe (Feprs) and total contents of Fe (TFe), which indicated that the geochemical cycling of these P fractions and Fe fractions are likely closely related and active in the soils and sediments. Calcium bound P (Ca-P) was significantly correlated with magnate (Femag) and Feprs, which may be due to the correlation between their background values in this area. The contents of active P including loosely sorbed P (L-P), Al-P, and Fe-P in the reservoir’s sediments, were significantly higher than those in the upstream soils and sediments (P < 0.05). However, Ca-P and residual P (Res-P) in soil and sediment samples was no significant difference between reservoir and its upstream (P=0.309 > 0.05 and P=0.748 > 0.05, respectively). Construction of reservoir has played a certain role in intercepting P, especially bioavailable P, transferred from upstream soils and riverine sediments. The contents of highly active Fe fractions including easily reducible (amorphous) Fe oxide (Feox1), reducible (crystalline) Fe oxide (Feox2) and Fecarb (P < 0.01) and other Fe fractions (p < 0.05) in the sediments of the reservoir were significantly higher than those in the soil or sediment samples from upstream. This indicated that all Fe fractions migrated in the river were affected by the dam interception. The effects of dam interception would affect the bioavailability of P and Fe, and enhance the cycling of nutrients in the region. Finally, this also effects on the bioavailability and cycling of P and Fe in the downstream rivers, and even the oceans.